The Long-Term Impact of Parental Divorce on Child Development - Putri Sahara; Izzagita Izzagita (Inovan Publisher, 2025)
Parental divorce has a significant impact on children's development, affecting their psychological and social aspects. The main issue raised is how divorce affects children's emotions and behavior, as well as the long-term consequences that may arise due to changes in family dynamics. The aim of this research is to explore the impact of divorce on children, with a focus on changes in behavior and emotional stability. Research goals include identifying factors that influence children's development after divorce and understanding how they adapt to these changes. The method used in this research is a literature review, where the author collects and analyzes various relevant literature sources related to the impact of divorce on children. The search was carried out via Google Scholar with keywords such as and